Modeling of the potential of the gravitational field at the upper boundary of the region with the existence of a subterranean anomaly (International Journal of Mathematics and Physics, 2018)
Abstract. All of humanity's activities are tied to fuel. Previously, it was coal, now it is oil. In order to find oil or coal in the earth's interior, preliminary analysis and calculations are necessary to confirm their existence, their size, location, type of mineral and much more. The aim of the study is to improve existing models of calculations for the search for minerals. To date, there are many methods and approaches to solving the problem, but they are not yet accurate enough. We solve the inverse problem of gravimetry, based on measurements of the Earth's gravitational field. At this stage, we carefully investigate the direct problem, without affecting the inverse. In the course of the study, we found interesting facts. Namely, the gravitational field on the Earth's surface with a different location of the anomaly has a very unpredictable result. The results of this study showed that lateral boundaries should be 30-50 times farther from the anomaly, with respect to the diameter of the anomaly. In addition, it reveals that the anomaly should be located in the middle of the area. This gives us the most plausible result.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть